2011
DOI: 10.2215/cjn.10511110
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Follistatin in Patients with Chronic Kidney Disease

Abstract: SummaryBackground and objectives Follistatin mediates muscle growth and bone mineralization. At present, it is unknown whether circulating follistatin levels are altered in chronic kidney disease (CKD) or links to CKD risk factors and outcomes.Design, setting, participants, & measurements Plasma follistatin levels were cross-sectionally analyzed in relation to protein-energy wasting (PEW), handgrip strength (HGS), bone mineral density (BMD), and inflammatory markers in 280 CKD stage 5 patients, 32 CKD stage 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…In several studies follistatin was not found to reflect dynapenia in older women or men [2, 31]. Interestingly, Miyamoto et al reported negative association between plasma follistatin and muscle strength in patients with chronic kidney disease, which is not consistent with observed effects of follistatin in inducing muscle hypertrophy [38]. Likewise, Liaw et al [35] found a negative correlation between follistatin and gait speed among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies follistatin was not found to reflect dynapenia in older women or men [2, 31]. Interestingly, Miyamoto et al reported negative association between plasma follistatin and muscle strength in patients with chronic kidney disease, which is not consistent with observed effects of follistatin in inducing muscle hypertrophy [38]. Likewise, Liaw et al [35] found a negative correlation between follistatin and gait speed among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also reported that serum levels of follistatin were not different among young males, older men with mild sarcopenia, and older men with severe sarcopenia [ 40 ]. However, a negative correlation between follistatin and gait speed was observed in older adults and patients with chronic kidney disease [ 47 , 48 ]. These conflicting results might be affected by the fact that TGF-β member (e.g., GDF-8, GDF-15, and Activin A) status may be accompanied by an increase in follistatin [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a negative correlation between follistatin and gait speed was observed in older adults and patients with chronic kidney disease [ 47 , 48 ]. These conflicting results might be affected by the fact that TGF-β member (e.g., GDF-8, GDF-15, and Activin A) status may be accompanied by an increase in follistatin [ 47 ]. However, the present study was unable to address the question of the causality of muscle growth factors in sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin, a protein that suppresses muscle growth, is another potential therapeutic target to inhibit. We recently showed that circulating levels of follistatin, a myostatin binder, were increased in wasted and inflamed incident dialysis patients, and negatively associated with muscle strength (7), suggesting a potential role of this molecular pathway in uremic PEW. In mice with CKD, myostatin inhibition by antimyostatin peptibody not only suppressed IL-6 and TNF but also prevented muscle atrophy (8).…”
Section: Pharmacological and Nutritional Treatment Of Uremic Inflammamentioning
confidence: 99%
“…Several names have been previously used to refer to this syndrome e.g., uremic malnutrition (5), protein-energy malnutri-tion (6), or malnutrition inflammation complex (1). To come to a more exact definition, the International Society of Renal Nutrition and Metabolism proposed the term protein energy wasting (PEW) (7). This nomenclature more accurately reflects the clinical syndrome.…”
mentioning
confidence: 99%